Technical efficiency and socioeconomic effects on poverty dynamics among cassava-based farming households in rural Nigeria (2021)
Despite the large scale public and government investment to improve the livelihoods of smallholder farmers, rural poverty remains widespread in Nigeria. However, efficiency effects on the transitory poverty has not received much attention in the poverty literature in Nigeria due to lack of nationally representative panel data that can track the poverty status of households over time. Using a two-wave panel data between 2010 and 2015, technical efficiency effects on poverty dynamics of cassava-based rural households in Nigeria was therefore investigated. Results showed that 14.9 % of the cassava farming households moved into poverty while 31.6 % exited from poverty. In the long run, the probability that rural cassava-based farmers would be non-poor (74 %) was higher than those remaining in poverty. Two out of five (42.2%) cassava-based farmers who were always poor exited technical inefficiency. A large number of farmers were actively involved in mono-cropping and mixed cropping but 29.7%, 26.0% and 16.6% of those involved in mono-cropping were always poor, entered and exited poverty, respectively. Tertiary education, marital status, access to extension farm size, membership of association, farming systems and technical efficiency were factors influencing poverty transitions in rural Nigeria.